TRANSFER OF INDIGENOUS KNOWLEDGE: PELESTARIAN PENGETAHUAN LOKAL PADA INSTITUSI LOKAL BUNDO KANDUANG DI MINANGKABAU - M. Fadli M. Fadli (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
Abst ract This research aims to analyze transfer of Indigenous knowledge activities undertaken by local institutions Bundo Kanduang in preserving indgenous knowledge ‘Adaik Salingka Nagari’. This research background consistency Bundo Kanduang in sustaining the cultural values of the policy in the midst of the battle the wave of globalization and Westernization in Minangkabau community. This research use the paradigm of constructivism. The research method used is qualitative method with the case study approach is used to express the reality in the field. Research data collected through observation, interviews, and documentation study. The conclusions of this research are as follows: local knowledge transfer activities undertaken by Bundo Kanduang as individuals within the family nucleus (nuclear family), and the family house (complex family), as organizations in the public, and education institutions, sharing knowledge Adaik Salingka Nagari Bundo Kanduang in organizations is done, and the exchange of knowledge, done by exchanging experiences with other organizations that are similarly engaged in community empowerment.